Migration of an IUD into the Myometrium Associated with a Painful Ovarian Cyst: A Case Report - Dagbesse Elysee Boko Dagoun; Yaya Samake; Michele Benie Menin-Messou; Clausen Georgie M’Bro; Narcisse Kouadio Kouadio; Lydie Estelle Djanhan (European Scientific Journal, ESJ, 2026)
The intrauterine device (IUD) is one of the most effective and widely used contraceptive methods worldwide. Secondary migrations are varied but rare when involving the myometrium, according to the literature. We report the clinical case of a 22-year-old patient, gravida 2, para 2, with a history of cesarean section eleven (11) months earlier, (during which an IUD had been inserted). she had consulted for isolated pelvic pain. Pelvic ultrasound incidentally revealed an IUD migrating into the myometrium, associated with a large ovarian cyst. The diagnosis was confirmed during exploratory laparotomy, which allowed for cystectomy followed by IUD removal. Histological examination of the ovarian cyst revealed a benign serous cystadenoma. Postoperative recovery was uneventful.